2017
DOI: 10.4013/nbc.2017.123.02
|View full text |Cite
|
Sign up to set email alerts
|

Ground-dwelling spiders (Arachnida, Araneae) in different vegetational formations in a Neotropical floodplain

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution 4.0 International (CC BY 4.0), which permits reproduction, adaptation, and distribution provided the original author and source are credited. Ground-dwelling spiders (Arachnida, Araneae) in different vegetational formations in a Neotropical floodplain Aranhas de solo (Arachnida, Araneae) em diferentes formações vegetacionais em uma planície de inundação Neotropical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…According to Lessard-Therrien et al (2018), the structure and ecological conditions of habitats are fundamental for determining the occurrence of spiders, since, for the most part, they are generalist predators that use a wide variety of prey, even if prey populations are small (Sunderland & Samu 2003). The dominance of hunting spiders found in this study is common in studies investigating the composition and structure of spider assemblages (Castilho et al 2005, Battirola et al 2004, Sena et al 2010, Anjos et al 2017, Yamazaki et al 2017.…”
Section: Urban Forest Fragmentsmentioning
confidence: 64%
See 2 more Smart Citations
“…According to Lessard-Therrien et al (2018), the structure and ecological conditions of habitats are fundamental for determining the occurrence of spiders, since, for the most part, they are generalist predators that use a wide variety of prey, even if prey populations are small (Sunderland & Samu 2003). The dominance of hunting spiders found in this study is common in studies investigating the composition and structure of spider assemblages (Castilho et al 2005, Battirola et al 2004, Sena et al 2010, Anjos et al 2017, Yamazaki et al 2017.…”
Section: Urban Forest Fragmentsmentioning
confidence: 64%
“…The assemblage composition and the most abundant families in these fragments correspond to taxa commonly sampled in studies evaluating the ground assemblages of spiders in the state of Mato Grosso (e.g. Castilho et al 2005, Battirola et al 2010, Anjos et al 2017. Some of these families have specific behaviors or characteristics, such as the Theridiidae, key insect predators in many ecosystems, which are among the few families of spiders with a high degree of myrmecophagy (Liu et al 2016).…”
Section: Urban Forest Fragmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, their numbers decrease in dense forests, which is in agreement with the results observed in our study, where highest number of this family were found in more open canopy sites. The same finding was observed in areas with different vegetation in neotropical floodplains (dos Anjos et al ., ). The guild specialist was represented mainly by the myrmecophagic species Zodarion germanicum (C. L. Koch, 1837), which is strongly associated with ants.…”
Section: Discussionmentioning
confidence: 97%